2020
DOI: 10.3390/jcm9123805
|View full text |Cite
|
Sign up to set email alerts
|

Sufficient Thrombin Generation Despite 95% Hemodilution: An In Vitro Experimental Study

Abstract: Guidelines for the treatment of severe bleeding comprise viscoelastic-test-guided use of coagulation factor concentrates as part of their recommendations. The aim of this study is to investigate the effects of substituting fibrinogen, prothrombin complex concentrate, and a combination of both on conventional coagulation tests, viscoelastic test results, and thrombin generation. Blood was drawn from seven healthy volunteers to obtain platelet-free plasma, which later was diluted by replacing 40%, 60%, 80%, 90%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 45 publications
2
22
0
3
Order By: Relevance
“…Our study revealed prolonged EXTEM CT values in the HES group despite of no differences in PT between the groups. Although EXTEM CT values primarily represent clot initiation dynamics, a relevant influence of the substrate fibrinogen on EXTEM CT has been described before [ 30 , 31 ]. Consequently, current guidelines for the management of major bleeding recommend further procoagulant medication only once fibrinogen levels, as represented by FIBTEM MCF, have been corrected [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed prolonged EXTEM CT values in the HES group despite of no differences in PT between the groups. Although EXTEM CT values primarily represent clot initiation dynamics, a relevant influence of the substrate fibrinogen on EXTEM CT has been described before [ 30 , 31 ]. Consequently, current guidelines for the management of major bleeding recommend further procoagulant medication only once fibrinogen levels, as represented by FIBTEM MCF, have been corrected [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…If SLT are useful for the diagnosis of coagulopathy or to guide hemostatic therapy is questionable [20,22,23]; their turnaround times of 45-60 min disqualify SLT, as median time to death due to exsanguination was 106 min [24]. However, if no other laboratory test is available, SLT may be preferable to no testing [22].…”
Section: Definitionsmentioning
confidence: 99%
“…[22] Perioperative use of SLT Review Gratz J et al J Clin Med. 2020 [23] Thrombin generation Laboratory, healthy volunteers Holcomb JB et al JAMA. 2015 [24] ratio Pragmatic, phase 3, multisite, randomized, clinical Connelly CR et al J Surg Res.…”
Section: Lier/friesmentioning
confidence: 99%
See 2 more Smart Citations